Exploring Digital Marketing Strategies for Crisis Recovery in South Jakarta’s Culinary Tourism - Putra, Halim Dwi Putra (LifeSciFi, 2025)
Culinary tourism in South Jakarta, a vibrant hub blending traditional and modern food services, has been reshaped by digital marketing, particularly amid boycott movements targeting certain businesses. These socio-political disruptions have highlighted gaps in how food services manage reputational crises and shifting consumer behaviour, especially among foreign workers. This study explores the interplay between culinary tourism and digital marketing in South Jakarta’s traditional and online food sectors, focusing on post-boycott recovery strategies and consumer responses. Employing a qualitative-comparative case study approach, data were gathered through semi-structured interviews with food service providers and digital marketing experts, complemented by online content analysis of customer reviews and campaign materials. Findings reveal that online food services effectively utilized targeted social media campaigns and influencer partnerships to restore consumer trust, while traditional vendors struggled due to limited digital literacy. However, traditional vendors leveraging authenticity and cultural heritage through digital storytelling showed recovery potential. The study expands the theoretical framework of digital culinary tourism by incorporating post-crisis consumer perceptions and emphasizes the need for culturally sensitive digital strategies. It advocates for capacity-building initiatives to empower traditional vendors, ensuring competitiveness in a digitally driven market.